At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
f(h) = -6h - 2/3
For f(-3), anywhere we see h in the equation we substitute -3.
f(-3) = -6(-3) - 2/3 = 18 -2/3 = 17 1/3.
f(-3) = 17 1/3 or 52/3.
So that's our answer.
For f(-3), anywhere we see h in the equation we substitute -3.
f(-3) = -6(-3) - 2/3 = 18 -2/3 = 17 1/3.
f(-3) = 17 1/3 or 52/3.
So that's our answer.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.